Expanding schooling opportunities for 4-year-olds - Edwin Leuven; Mikael Lindahl; Hessel Oosterbeek; Dinand Webbink (Institute for the Study of Labor (IZA), 2006)
This study presents quasi-experimental estimates of the effect of expanding early schooling enrollment possibilities on early achievement. It exploits two features of the school system in Holland. The first is rolling admissions; children are allowed start school immediately after their 4th birthday instead of at the beginning of the school year. The second is that children having their birthday before, during and after the summer holiday are placed in the same class. These features generate sufficient exogenous variation in children's maximum length of schooling to identify its effects on test scores. Making available one additional month of time in school increases language scores of disadvantaged pupils by 0.06 of a standard deviation and their math scores by 0.05 of a standard deviation. For non-disadvantaged pupils we find no effect.
urn:nbn:de:101:1-2008072446
Keywords: 330